Experience of Applying Active Learning Models in the Development of Clinical Skills of Nursing Students: Phenomenological Study - Edison Kabak (GLOBAL HEALTH SCIENCE GROUP, 2026)
Background: The active learning model in nursing education is believed to be able to strengthen clinical skill development through hands-on experience and student engagement. However, the understanding of students' subjective experiences in applying this model is still limited. Objective: This study aims to explore the experiences of nursing students in applying active learning models to enhance their clinical skills. Methods: The study used a phenomenological approach with an in-depth purposive sampling technique, interviews with 12 Wamena D-III Nursing students. The data were analyzed thematically to identify students' experiences, strategies, and reflections in clinical practice. Results: Students report that active engagement, decision-making, role adaptation, and self-reflection are key aspects of clinical skills development. The application of active learning helps improve technical competence, confidence, communication, and readiness to face the challenges of clinical practice. Conclusion: Active learning is effective in building students' clinical skills comprehensively, as well as forming professional competencies that are adaptive, reflective, and. Prepared to handle the complexities of clinical practice.